Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1093/jamia/ocac046
|View full text |Cite
|
Sign up to set email alerts
|

Comparing medical history data derived from electronic health records and survey answers in the All of Us Research Program

Abstract: Objective A participant’s medical history is important in clinical research and can be captured from electronic health records (EHRs) and self-reported surveys. Both can be incomplete, EHR due to documentation gaps or lack of interoperability and surveys due to recall bias or limited health literacy. This analysis compares medical history collected in the All of Us Research Program through both surveys and EHRs. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…As we used whole genome sequence data, differences in OR across ancestries cannot be attributed to uncertainty in imputation of genotypes, but rather solely to differences in LD with causal variation. However, the availability of EHR data, and therefore the number of cases and controls, may be associated with self-identified race or ancestry, which further complicates interpretation of the results 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we used whole genome sequence data, differences in OR across ancestries cannot be attributed to uncertainty in imputation of genotypes, but rather solely to differences in LD with causal variation. However, the availability of EHR data, and therefore the number of cases and controls, may be associated with self-identified race or ancestry, which further complicates interpretation of the results 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The AOU dataset contains a rich database of ICD 9 and 10 codes, CPT codes, and Logical Observation Identifiers Names and Codes (LOINC). As the completeness of this data varies among participants 25 we attempted to widen our net by creating concept sets based on the original ICD 9 and CPT codes, incorporating the related ICD 10 codes and LOINC codes. Each concept set relates to a different table from the word files provided by the algorithm’s authors (Supplemental Tables S2-S10).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study of the All of Us research program overall found that strength of concordance between EHR-based diagnosis and survey data for diseases vary. 19 The authors suggest that survey data overall provides a useful avenue to augment EHR data through identifying missing records or diagnoses, and addressing biases in EHR data collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prior publication examining the concordance of self-reported and EHR data in All of Us showed that traditionally underreported EHR diagnoses such as myopia are low, while traditionally highly reported diagnoses such as cancer are high, suggesting that the data are appropriately collected. 19 Furthermore, issues with missing data could represent a systematic bias in EHR based kidney stone prevalence assessment globally. Finally, income and education were used as surrogates for financial ability, but net worth, which is likely a better indicator of socioeconomic status in this older population, could not be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The AoU medical history survey includes a self-report questionnaire about diagnoses of over 150 medical conditions organised into 12 disease categories 23. We will use a combination of self-reported responses to the medical history survey and data from diagnosis codes in the EHR data to ascertain the presence of all comorbidities, such as cardiovascular risk factors, including hypertension (OMOP code 316866), hyperlipidaemia (OMOP code 432867) and type 2 diabetes mellitus (OMOP code 201826), and use self-reported data from the lifestyle survey to ascertain smoking status.…”
Section: Methods and Analysismentioning
confidence: 99%